1996
DOI: 10.1021/bk-1996-0635.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Gel Chromatography as an Analytical Tool for Characterization of Size and Molecular Mass of Proteins

Abstract: Although experience with watersoluble, globular proteins supports Stokes radius as an appropriate size parameter, governing elution position, for both classical and HPLC gel columns, extrapolation of this concept to other kinds of conformation and substances requires caution. Current evidence suggests the viscosity based Stokes radius as the best suited size parameter for many flexible macromolecules (guanidinium HCl denatured proteins, dextrans), whereas many detergent micelles and detergent solubilized membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The weight to put on this deduction is limited, because the older data are based on cross-linking experiments, whereas ours are based on gel filtration, which is known to deviate from the theoretical when the protein concerned is not spherical (e.g. le Maire et al, 1996). Indeed, naphthalene dioxygenase oxygenase was long considered to have an α # β # structure and was shown to be α $ β $ only when the crystal structure became available (Kauppi et al, 1998) ; the oxygenase was found not to be spherical but mushroom-shaped.…”
Section: Discussionmentioning
confidence: 99%
“…The weight to put on this deduction is limited, because the older data are based on cross-linking experiments, whereas ours are based on gel filtration, which is known to deviate from the theoretical when the protein concerned is not spherical (e.g. le Maire et al, 1996). Indeed, naphthalene dioxygenase oxygenase was long considered to have an α # β # structure and was shown to be α $ β $ only when the crystal structure became available (Kauppi et al, 1998) ; the oxygenase was found not to be spherical but mushroom-shaped.…”
Section: Discussionmentioning
confidence: 99%
“…Gel filtration chromatography indicated that active TsaR is a monomer in solution, though le Maire et al (18) warn of errors sometimes encountered with this method. TsaR as the active monomer differs from several LysR-type regulators.…”
Section: Fig 3 Band Shift Assays With Tsarmentioning
confidence: 99%
“…This difference could be due to a difference in the Stokes radii of the complexes, to electrostatic repulsion between the ATPase⅐A8-35 complex and negative charges on the gel pore walls (either residual charges on the matrix itself or charges due to adsorbed A8-35 molecules), or both. 2 Correct calibration of size exclusion columns in terms of Stokes radii is known to be a difficult task (22,(62)(63)(64)(65). However, another feature of the chromatograms for diluted delipidated ATPase complexes was the larger width of the main ATPase peak following trapping by amphipols.…”
Section: Stabilization By Amphipols Of Sr Camentioning
confidence: 99%